2002
DOI: 10.4049/jimmunol.168.11.5928
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of p21 (WAF-1/Cip1) Does Not Induce Systemic Autoimmunity in Female BXSB Mice

Abstract: Cell cycle, apoptosis, and replicative senescence are all influenced by the cyclin-dependent kinase inhibitor, p21. It was previously reported that deletion of p21 in 129/Sv × C57BL/6 mixed genetic background mice induced a severe lupus-like disease, almost exclusively in females. However, we did not confirm this finding in an independently derived stock of 129/Sv × C57BL/6 p21−/− mice. To further address this discrepancy, we examined the effects of p21 deletion in BXSB female mice that develop late-life, mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…In addition, mice with the p21 gene deleted in the 129/Sv ϫ C57BL/6 mixed genetic background had more CD44 high , CD4 ϩ T cells in their spleen than p21 ϩ/ϩ mice (12). These discrepancies may be related to the use of knockout animals to investigate the involvement of p21 WAF1/CIP1 in autoimmune phenomena (12,15,50). Indeed, backcrosses can have altered the autoimmune genetic background and led to conflicting data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice with the p21 gene deleted in the 129/Sv ϫ C57BL/6 mixed genetic background had more CD44 high , CD4 ϩ T cells in their spleen than p21 ϩ/ϩ mice (12). These discrepancies may be related to the use of knockout animals to investigate the involvement of p21 WAF1/CIP1 in autoimmune phenomena (12,15,50). Indeed, backcrosses can have altered the autoimmune genetic background and led to conflicting data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above studies, BXSB p21 Ϫ/Ϫ mice were generated, and it was reported that p21 deficiency did not affect the mild autoimmunity that characterizes BXSB female mice (10). On the basis of this work, the authors concluded that deletion of p21 is unrelated to autoimmunity induction and claimed that previous data showing an autoimmune predisposition in p21 Ϫ/Ϫ mice could be confounded by the autoimmunity predisposition of mixed background mice (10).…”
mentioning
confidence: 88%
“…Abnormalities in some of these genes, such as C1q, DNase1, and Fas, have been identified in rare patients with SLE or lymphoproliferative disorders (20 -23). Murine studies have also emphasized the importance of background genes in determining the phenotypes resulting from single gene alterations (7,24,25). The (NZB ϫ NZW)F 1 mouse has been carefully analyzed genetically because it represents a polygenic model for SLE (1,26,27).…”
mentioning
confidence: 99%